P134 Effects of post-thawing transport and donor mare age on pregnancy outcomes of vitrified IVP equine embryos produced in a commercial ICSI laboratory - P. Arrondo Navarrete; S.A. Stampfli; J. Sieber; A. Ferrante; A. Ballester; M.B. Rodriguez (Journal of Equine Veterinary Science, 2026)

P18-20 Building Bridges in Tobacco Harm Reduction: A Global Interlaboratory Initiative for Standardized Smoke and Aerosol Exposure Assessment - M. Caruso; R. Emma; P. Zuccarello; S. Rust; G. Carota; K. Poulas; F. Zadjali; A. Sun; V. Volarevic; R. Lesmana; M. Tobi; K. Mesiakaris; et al. (Toxicology Letters, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

Comparison of different cryoprotectants for freezing donkey jack (Equus asinus) semen - Santiago L Bruno; Deborah M Neild; Jessica P Plaza; Alejandro A Ferrante; María I Carretero; Gustavo EA Olivieri; Carolina P Bianchi; Marcelo H Miragaya (Journal of Equine Veterinary Science, 2023)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

Modeling hypoxia-related inflammation scenarios - P. Ferrante; L. Preziosi; M. Scianna (Mathematical Biosciences, 2023)

A novel morphological phenotype does not ensure reduced biotic resistance on an oceanic island - M. Ferrante; R. Nunes; L. Lamelas-López; G. L. Lövei; P. A. V. Borges (Biological Invasions, 2022)

Correction to: Sant’Imbenia (Alghero): further archaeometric evidence for an Iron Age market square - M. Clemenza; B. Billeci; M. Carpinelli; M. Ferrante; E. Fiorini; G. Gasperetti; S. Nisi; P. Oliva; V. Sipala; P. R. Trincherini; I. M. Villa; M. Rendeli (Archaeological and Anthropological Sciences, 2021)

Sant’Imbenia (Alghero): further archaeometric evidence for an Iron Age market square - M. Clemenza; B. Billeci; M. Carpinelli; M. Ferrante; E. Fiorini; G. Gasperetti; S. Nisi; P. Oliva; V. Sipala; P. R. Trincherini; I. M. Villa; M. Rendeli (Archaeological and Anthropological Sciences, 2021)
Lead isotope compositions were determined for 18 metal objects from the archaeological site of Sant’Imbenia, NW Sardinia, dating to the end of the ninth century BCE onwards. The provenance of some objects is unambiguously traced to SW Sardinia; other objects could derive either from central Sardinia or the Iberian coastal ranges. The variety of the provenances attests to a wide trade network that spanned the entire island of Sardinia and extended to the Iberian sites.

Lipidomics reveals specific lipid molecules associated with cold stress syndrome in the Florida manatee (Trichechus manatus latirostris) - Emily K. Griffin; Kaylie Anne Costa; Juan J. Aristizabal-Henao; Michael P. Napolitano; Margaret E. Hunter; Jason A. Ferrante; John A. Bowden (Marine Biology, 2021)

Characterisation of Pseudomonas syringae isolates from apricot orchards in north-eastern Italy - D. Giovanardi; P. Ferrante; M. Scortichini; E. Stefani (European Journal of Plant Pathology, 2018)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Emended description of Pseudomonas syringae pv. avellanae, causal agent of European hazelnut (Corylus avellana L.) bacterial canker and decline - M. Scortichini; P. Ferrante; L. Cozzolino; A. Zoina (European Journal of Plant Pathology, 2016)

Pseudomonas syringae pv. actinidiae strains isolated from past and current epidemics to Actinidia spp. reveal a diverse population structure of the pathogen - P. Ferrante; Y. Takikawa; M. Scortichini (European Journal of Plant Pathology, 2015)

Effects of Pseudomonas fluorescens Seed Bioinoculation on Heavy Metal Accumulation for Mirabilis jalapa Phytoextraction in Smelter-Contaminated Soil - M. Petriccione; D. Di Patre; P. Ferrante; S. Papa; G. Bartoli; A. Fioretto; M. Scortichini (Water, Air, & Soil Pollution, 2013)

The interactions of age, sex, body mass index, genetics, and steroid weight-based doses on tacrolimus dosing requirement after adult kidney transplantation - P. Stratta; M. Quaglia; T. Cena; R. Antoniotti; R. Fenoglio; A. Menegotto; D. Ferrante; A. Genazzani; S. Terrazzino; C. Magnani (European Journal of Clinical Pharmacology, 2012)

JC virus small tumor antigen promotes S phase entry - M Safak; R Biffi; S Woolridge; I Kudret; IK Sariyer; I Akan; P Ferrante; K Khalili; M Safak (Journal of NeuroVirology, 2004)

Agnoprotein and its coding sequences play regulatory roles in JC virus gene transcription and replication in glial cells - M Safak; R Biffi; S Radhakrishnan; S Woolridge; I K Sariyer; I Akan; J Gordon; S Amini; P Ferrante; K Khalili (Journal of NeuroVirology, 2004)

Subgrouping of human rotavirus strains by complement fixation, indirect double-antibody sandwich enzyme-linked immunosorbent assay and solid-phase immune electron microscopy - G. Gerna; M. Torsellini; N. Passarani; M. Battaglia; E. Percivalle; A. Sarasini; D. Torre; P. Ferrante (Archives of Virology, 1984)